1995
DOI: 10.1103/physrevc.51.103
|View full text |Cite
|
Sign up to set email alerts
|

Study ofCd110from theIn

Abstract: The p-ray transitions following the P decay of In (half-life 69 min) were observed using Compton-suppressed Ge detectors. The activity was produced by the Cd(p, 2n) reaction at a bombarding energy of 18.9 MeV. Singles in multispectra mode and pp-coincidence experiments were performed. Approximately 150 transitions were assigned to Cd, based on their measured halflife and/or observation in coincidence with well-known lines. The logzo(ft) values of nearly all observed levels were determined and an analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The 2 + 1 to ground state transition of 45 W.u. is typical of, but somewhat larger than, such transitions in vibrational nuclei in this region [15][16][17][18][19][20][21]. The B(E2) values from the triplet of 0 + , 2 + and 4 + levels around 1100 keV also resemble what is found for typical vibrational nuclei near A ∼ 100, namely a 4 + 1 → 2 + 1 transition that exhausts the majority of the two-phonon to one-phonon strength while the decays of the two-phonon candidate 2 + 2 and 0 + 2 levels are substantially weaker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 + 1 to ground state transition of 45 W.u. is typical of, but somewhat larger than, such transitions in vibrational nuclei in this region [15][16][17][18][19][20][21]. The B(E2) values from the triplet of 0 + , 2 + and 4 + levels around 1100 keV also resemble what is found for typical vibrational nuclei near A ∼ 100, namely a 4 + 1 → 2 + 1 transition that exhausts the majority of the two-phonon to one-phonon strength while the decays of the two-phonon candidate 2 + 2 and 0 + 2 levels are substantially weaker.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison to 98 Ru on the one hand, where vibrational structure above the two phonon level seems completely destroyed, and the Cd nuclei from 110−118 Cd [15][16][17][18][19][20][21] where good candidates for three and higher phonon levels with substantial fractions of the vibrator collectivity are known, suggests that 102 Ru has an intermediate structure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high-statistics data for low-intensity transitions following β + /EC , and 2480-keV (6 + 1 ) levels as members of the three-phonon quintuplet [3,18,19,23,25].…”
mentioning
confidence: 99%
“…Kawase et al in 1972 [9] first proposed a doublet of levels with spins 0 + and 3 − at 2079 keV. This was later confirmed [1][2][3]. An upper limit was determined by Corminboeuf et al, Ref [4], for the 1421.1-keV transition from the 2078.6-keV 0 + level.…”
Section: Resultsmentioning
confidence: 73%
“…Experiments with the (α, 2n) reaction by Kern et al [1], β decay measurements by Bertschy et al [2], light-ion induced reactions and decays by Kumpulainen et al [3], and an (n, n ′ γ) study by Corminboeuf et al [4] have identified multi-phonon states in the 110 Cd decay scheme indicating vibrational motion. The Cd nuclei have been considered as some of the best examples of near-harmonic vibrational behavior [5].…”
Section: Introductionmentioning
confidence: 99%